The Role of Multi-modality Imaging in the Diagnosis of Cardiac Amyloidosis: A Focused Update - Khanna, Shaun; Wen, Ivy; Bhat, Aditya; Chen, Henry H. L.; Gan, Gary C. H.; Pathan, Faraz; Tan, Timothy C. (Frontiers in Cardiovascular Medicine, 2020)
Cardiac Amyloidosis (CA) is a unique disease entity involving an infiltrative process, typically resulting in a restrictive cardiomyopathy with diastolic heart failure that ultimately progresses to systolic heart failure. The two most common subtypes are light-chain and transthyretin amyloidosis. Early diagnosis of this disease entity, especially light-chain CA subtype, is crucial, as it portends a poorer prognosis. This review focuses on the clinical utility of the various imaging modalities in the diagnosis and differentiation of CA subtypes. This review also aims to highlight the key advances in each of the imaging modalities in the diagnosis and prognostication of CA.